Total Knee Arthroplasty in Severe Valgus Osteoarthritis Excellent Early Results in a 90-Year-Old Patient with a Valgus Deformity of 47° - Petros Ismailidis; Rolf Kernen; Sebastian Andreas Mueller (Case Reports in Orthopedics)
Grade III valgus deformity (tibiofemoral alignment > 20°) is present in only 0.5% of patients receiving total knee arthroplasty. Furthermore, cases with a valgus deformity exceeding 40° are even rarer. Since they mostly affect elderly, polymorbid patients, successful outcome means a great challenge. We report on a case of a 90-year-old patient with a valgus deformity of 47°. The patient was preoperatively restricted to a wheel chair, unable to walk, and only able to stand for a few seconds. The maximal knee flexion was 100°, and there was an extension deficit of 15°. The WOMAC score was 91; the EQ-5D-5L Index was 0.048. She was treated with a constrained hinged prosthesis. Postoperatively, the axis was 6° valgus. After 3 months of rehabilitation, she was independent using a wheeled walker. The maximal flexion of the knee was 110° and there was no extension deficit. The WOMAC score was 45; the EQ-5D-5L Index was 0.813. This case demonstrates the possibility of a satisfactory result and an improvement in quality of life and mobility with a plausible timetable and with reasonable use of resources even in advanced age and severe valgus deformity.